Local government perspectives on rural retirement migration and social sustainability. Issue 1 (2nd January 2019) - Winterton, Rachel; Butt, Andrew; Jorgensen, Bradley; Martin, John
ABSTRACT: Within the policy and academic literature, the impact of rural retirement migration (RRM) on community sustainability has been questioned. This qualitative study investigated the perceived impact of retirement migration on rural social sustainability from a local government perspective. Focus groups were conducted with local government senior managers and community services staff (n = 39) across six rural local government areas in one Australian state. Data were analysed against the three components of rural social sustainability (equity, community and rurality) proposed by Jones and Tonts [1995. "Rural Restructuring and Social Sustainability: Some Reflections on the Western Australian Wheatbelt." Australian Geographer 26: 133–140]. While RRM is perceived to benefit rural community capacity to facilitate or maintain equity, community and rurality, it also presents challenges for local government. Participants suggested that capacity to facilitate equity, community and rurality in contexts of RRM was impacted by uncertainty around future impacts of RRM on population ageing, increasing advocacy and expectations of older in-migrants, and the impact of RRM on rural heterogeneity. These issues required local governments to think critically about how to accommodate and manage the needs and expectations of older in-migrants, while mediating potential impacts associated with RRM.